Challenges and opportunities for conserving biodiversity through volunteer initiatives and international cooperation projects - Jiménez Escobar, María Dolores; Delgado Sáez, Juan Antonio (Revista Española de Desarrollo y Cooperación, 2025)
The main objective of this study is to present two examples of development cooperation projects for the conservation of biodiversity carried out in Arequipa (Peru) by students of the Biology Department of the UCM, within the framework of the International Volunteer Programme of the Public Universities of Madrid and in collaboration with the UNSA University. The objective of the first example is to protect the Tara tree (Caesalpinia spinosa), the only tree species associated with the tropical ecosystem of the "cloud forest" or "Lomas" in Atiquipa. The second objective was to create a biodiversity database for the Arequipa region. Both projects are currently in progress.
Keywords: Biodiversity conservation; Perú; cloud forest; database; international volunteering